Comparing the Effectiveness of Metformin–Acarbose and Metformin–Sulfonylurea Combination Therapies in Patients with Type 2 Diabetes Mellitus at Diponegoro National Hospital - Syarifah Khaerunnisa; Eva Annisaa'; Fitri Wulandari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: Diabetes mellitus is a major non-communicable disease and accounts for approximately 4% of deaths in Indonesia. The effectiveness of type 2 diabetes mellitus (T2DM) treatment is generally evaluated using HbA1c, fasting blood sugar (FBS), postprandial blood sugar (PPBS), and the incidence of hypoglycemia—the most concerning complication. Multiple combination therapy regimens are available, each with varying levels of effectiveness.Objectives: This study aimed to compare the effectiveness of metformin–sulfonylurea and metformin–acarbose combination therapies in T2DM patients, as measured by HbA1c, FBS, PPBS, and hypoglycemia incidence at Diponegoro National Hospital.Methods: A cross-sectional observational study with a retrospective design was conducted. Secondary data were collected between January 2021 and June 2023 using purposive sampling. Eligible patients had received regular drug therapy for at least three months.Results: Among patients receiving metformin–sulfonylurea, glycemic control was achieved in 82.3% for FBS, 82.3% for PPBS, and 48.4% for HbA1c, with 82.3% showing no hypoglycemia. In patients receiving metformin–acarbose, glycemic control was achieved in 66.1% for FBS, 67.7% for PPBS, and 32.3% for HbA1c, with 96.8% showing no hypoglycemia.Conclusion: Significant differences in effectiveness were observed between metformin–sulfonylurea and metformin–acarbose with respect to FBS and hypoglycemia incidence, whereas no significant differences were found for PPBS and HbA1c. These findings suggest that both regimens are generally effective. Metformin–sulfonylurea may be preferred when stricter glycemic control is desired, while metformin–acarbose may be more suitable for patients at higher risk of hypoglycemia.